2017
DOI: 10.1063/1.4977877
|View full text |Cite
|
Sign up to set email alerts
|

Anharmonicity of monolayer MoS2, MoSe2, and WSe2: A Raman study under high pressure and elevated temperature

Abstract: In this paper, the thermodynamic parameters such as Grüneisen parameters and anharmonicity are investigated utilizing pressure- and temperature-dependent Raman spectroscopy of monolayer transition-metal dichalcogenides MX2 (M = Mo, W; X = S, Se). The result indicates a good stability of these compounds in the pressure range of 0–9.0 GPa and the temperature range of 175–575 K. It is a general trend that Raman mode varies with temperature and pressure linearly for monolayer MX2, and the thermodynamic Grüneisen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 44 publications
6
58
0
Order By: Relevance
“…The measured Raman spectra of bare (orange) and AlO x -capped (blue) 1L MoSe 2 are displayed in Figure 1 c. The A 1 ′ Raman active mode (out-of-plane vibration of Se atoms) is observed at 240.2 cm –1 for 1L MoSe 2 , which is consistent with previous reports on the MoSe 2 1L. 42 45 We note that A 1 ′ notation of this Raman mode is valid for 1L and odd number of (few) layers, whereas it is labeled A 1g for bulk and even number of layers. 7 , 46 , 47 After capping the 1L MoSe 2 by AlO x , a blue shift of ∼1.15 cm –1 and broadening in the A 1 ′ Raman mode are observed, demonstrating strong doping dependence, as previously reported for 1L MoS 2 .…”
Section: Results and Discussionsupporting
confidence: 88%
“…The measured Raman spectra of bare (orange) and AlO x -capped (blue) 1L MoSe 2 are displayed in Figure 1 c. The A 1 ′ Raman active mode (out-of-plane vibration of Se atoms) is observed at 240.2 cm –1 for 1L MoSe 2 , which is consistent with previous reports on the MoSe 2 1L. 42 45 We note that A 1 ′ notation of this Raman mode is valid for 1L and odd number of (few) layers, whereas it is labeled A 1g for bulk and even number of layers. 7 , 46 , 47 After capping the 1L MoSe 2 by AlO x , a blue shift of ∼1.15 cm –1 and broadening in the A 1 ′ Raman mode are observed, demonstrating strong doping dependence, as previously reported for 1L MoS 2 .…”
Section: Results and Discussionsupporting
confidence: 88%
“…The vibrational frequencies from the rigid-ion model are in good agreement with the experimental data, as shown in Table 1. The calculated results from the DFT frame are about 9% lower than the experimental results, which is a well-known underestimation of the phonon frequency by using the PBE functional [43,44,45]. To study the behavior of the phonon structure in greater detail, we analyzed the pressure dependence of the phonon frequency at center point Γ.…”
Section: Resultsmentioning
confidence: 98%
“…Including both the laser intensity distribution I ( z ) and the induced temperature response T ( z ) in the Lorentzian Raman profile function in Equation leads to the following line shape function: I(),ωT=ccIoez/b2ωωoTz2+ΓTz/z2italicdz. The integral in z is defined by the laser spot size and c = 1/2 b . There are few reports on the inhomogeneous heating effects in TMDs, 73,74 although some of the reported phonon line shapes of the layered effect in TMDs exhibit asymmetric broadening 23,75–77 characteristic of an inhomogeneous laser heating effect. Huang et al 78 reported homogenous temperature‐dependent evolution of the Raman spectra of a chemical vapor deposition (CVD)‐grown monolayer WS 2 ; they showed the dependence of the Raman shifts of the modes on the three‐phonon process and the coefficient of thermal expansion.…”
Section: Laser Flux‐induced Effect: Inhomogeneous Heatingmentioning
confidence: 99%